2017
DOI: 10.3892/etm.2017.4904
|View full text |Cite
|
Sign up to set email alerts
|

Wogonoside alleviates inflammation induced by traumatic spinal cord injury by suppressing NF-κB and NLRP3 inflammasome activation

Abstract: Abstract. Wogonoside possesses anti-oxidative, anti-inflammatory, anti-allergy and anti-tumor properties. The aim of the present study was to evaluate whether wogonoside alleviates spinal cord injury (SCI)-induced inflammation via nuclear factor (NF)-κB and nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activation. Sprague-Dawley rats were positioned in the jaws of a calibrated aneurysm clip with a closing pressure of 55 g. The jaws were placed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Based on previous study [ 16 ], we performed qPCR of markers of the M1 phenotype microglia/macrophage (inducible nitric oxide synthase, iNOS) [ 4 , 13 , 25 ] or M2 phenotype microglia/macrophage (arginase1, Arg1) [ 4 , 13 , 25 ] and calculated the ratio of Arg1/iNOS mRNA to analyze the change of microglia/macrophage polarization 3 days post injury. We found that BAY 11-7082 ( P < 0.05) or A438079 ( P < 0.01) increased the ratio of Arg1/iNOS mRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on previous study [ 16 ], we performed qPCR of markers of the M1 phenotype microglia/macrophage (inducible nitric oxide synthase, iNOS) [ 4 , 13 , 25 ] or M2 phenotype microglia/macrophage (arginase1, Arg1) [ 4 , 13 , 25 ] and calculated the ratio of Arg1/iNOS mRNA to analyze the change of microglia/macrophage polarization 3 days post injury. We found that BAY 11-7082 ( P < 0.05) or A438079 ( P < 0.01) increased the ratio of Arg1/iNOS mRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated that NLRP3 inflammasome blockade with BAY 11-7082 or A438079 decreased the number of CD68-positive cells, indicating the suppression of microglia/macrophage activation. Moreover, we analyzed microglia/macrophage polarization through investigation of the ratio of Arg1/iNOS mRNA based on previous study [ 16 ]. BAY 11-7082 or A438079 increased the ratio of Arg1/iNOS mRNA in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is post-SCI activation of NLRP3 inflammasome in an animal model involving microglia and spinal cord tissue (Grace et al, 2016;Jiang et al, 2016;Zendedel et al, 2016). Further, previous studies have reported means of reducing neuroinflammation and promoting functional recovery in SCI animals by suppressing NLRP3 inflammasome activity (Qian et al, 2017;Zhu et al, 2017). Jiang et al (2017) reported that suppression of NLRP3 inflammasome activity to control neuroinflammation using the small-molecule inhibitor BAY 11-7082 or A438079 could attenuate mitochondria damage, alleviate SCI, and improve neuronal function restoration in a mouse model of SCI.…”
Section: Introductionmentioning
confidence: 99%